The Relationship between Psychology, Creativity Practices and Teacher Commitment in Visual Arts Education - Hakimi, Halim; Muhammad Khairullah, Muhammad Marzidi (Auricle Global Society of Education and Research, 2023)
This study analyzes the relationship between creativity practices and commitment among Visual Arts Education teachers in the Bintulu district, Sarawak. A quantitative approach using a survey research design was employed, involving 190 teachers from national schools. The findings of the study indicate a high level of creativity practices and commitment among teachers. There is a significant positive relationship between creativity practices and teacher commitment had been detected. The study suggests the importance of teacher commitment in enhancing creativity in Visual Arts Education for meaningful learning. Future research should explore other factors that influence creativity practices and teacher commitment. Visual Arts Education teachers can utilize this study to improve both curriculum and pedagogy.